Odpowiedzialność komornika sądowego za nieprawidłowe rozliczenie opłaty egzekucyjnej na podstawie przepisów kodeksu karnego skarbowego - Sakowicz, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article presents new types of criminal acts concerning the responsibility of a judicial enforcement officer for improper settlement of the enforcement fee under the provisions of the Fiscal Penal Code. The author analyses an element of new offences (Articles 57a and 57b of the Fiscal Penal Code) and makes a critical assessment of them in the context of the proportionality principle and the internal consistency of the provisions of the Fiscal Penal Code. In the final analysis the author comes to a conclusion that there is no rational justification for adopting new criminal liability offenses for judicial enforcement officer.
Keywords: a judicial enforcement officer; Fiscal Penal Code; the financial criminal liability; rational legislator